2005
DOI: 10.1038/sj.jp.7211352
|View full text |Cite
|
Sign up to set email alerts
|

Selective Serotonin Reuptake Inhibitor (SSRI) Use during Pregnancy and Effects on the Fetus and Newborn: A Meta-Analysis

Abstract: Selective serotonin reuptake inhibitors (SSRIs) are frequently used to treat depression during pregnancy and the postpartum period. These drugs are capable of crossing the placenta and being transferred to the newborn during lactation. This report reviews the available information regarding the effects of SSRIs on the fetus and newborn; including long-term neurodevelopmental outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
2
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(119 citation statements)
references
References 52 publications
6
106
2
5
Order By: Relevance
“…There is still controversy whether symptoms observed in neonates born to mothers to whom SSRI during pregnancy were administered, reflect neonatal withdrawal (enhanced clearance) or are the manifestation of persistent high SSRI concentrations with toxicity due to limited clearance (26). SSRIs undergo CYP2D6 dependent metabolic clearance.…”
Section: Discussionmentioning
confidence: 99%
“…There is still controversy whether symptoms observed in neonates born to mothers to whom SSRI during pregnancy were administered, reflect neonatal withdrawal (enhanced clearance) or are the manifestation of persistent high SSRI concentrations with toxicity due to limited clearance (26). SSRIs undergo CYP2D6 dependent metabolic clearance.…”
Section: Discussionmentioning
confidence: 99%
“…According to the majority of studies, the use of SSRIs and TCAs in pregnancy imposes no increased risk for malformations (Altshuler et al 2001;Alwan et al 2007;Austin and Mitchell 1998;Emslie and Judge 2000;Ericson et al 1999;Hogberg and Wang 2005;Kallen and Otterblad Olausson 2007;Koren et al 2005;Lattimore et al 2005;Malm et al 2005;Misri et al 2000a;Misri et al 2000b;Nordeng and Spigset 2005;Ramos et al 2008), although some reports have raised concerns about fetal cardiac effects, newborn persistent pulmonary hypertension, respiratory distress and other effects (ACOG 2006;Oberlander et al 2008). However, it is recommended to avoid paroxetine use among pregnant women or women planning to become pregnant, if possible (ACOG 2006).…”
Section: Pregnancymentioning
confidence: 99%
“…Several recent studies suggest that although individual SSRIs may confer an increased risk of some specific birth defects (as expressed by the odds ratios), there is only a slight effect on absolute risk (7)(8)(9). Others observed that third-trimester intake of SSRIs accounts for symptoms of poor neonatal adaptation (10 -14) and, consequently, higher-than-normal rates of admission to neonatal special care and intensive care units (10,15). According to a 2005 literature review, SSRI exposure is associated with an overall risk ratio of 3.0 (95% CI, 2.0 -4.4) for neonatal behavioral syndrome (12); one study also reported an alarming complication of persistent infantile pulmonary hypertension (16).…”
mentioning
confidence: 99%